CONCEPTS COMPETENCE AND COMPETENCE - Салиева Нигора Садиковна (Journal Park Publishing, 2023)
A brief overview of the use of the terms competence is given in this article. This article discusses the problem of the formation of competencies in a teacher, presents the types of competencies that contribute to improving the quality of activities and solving the problem of training a specialist. Modern society requires the formation of a competitive teacher who is able to respond to rapidly changing circumstances, where communicative competence occupies an important place. The competence of a teacher is his personality, in the structure of which his motivation, properties, the nature of his traits, psychological processes are distinguished.
Keywords: pedagogical competence, competence, model of pedagogical competence, pedagogical technique